Hubungan Tingkat Spiritual Terhadap Kualitas Hidup Penderita Diabetes Melitus di Masa Pandemi Covid-19 - Sukma Handayani; Yesi Hasneli; Yufitriana Amir (Indonesian Journal of Nursing Research (IJNR), 2022)
Diabetes Mellitus sufferers have endurance and weak bodies thus vulnerable to infection with Covid-19. Diabetes Mellitus has an impact on physical and psychological which causes a decrease in quality of life. Good quality of life is an optimal functional condition in terms of physical, psychological, environmental, social, and spiritual aspects. One of the important contributors to health-related quality of life for people with Diabetes Mellitus to maintain their quality of life is spirituality. Spirituality can improve the health of people with Diabetes Mellitus in the face of the Covid-19 pandemic. Objective: This study was to determine the relationship between people's spiritual level and quality of life in diabetes Mellitus during the Covid-19 pandemic. This study used a descriptive correlation method and a cross-sectional. The sample used as many as 121 people with a total sampling technique. The measuring instrument used is the WHOQOL-BREF and DSES questionnaires which have been tested for validity and reliability Test calculation Chi-Square shows that there is a significant relationship between spiritual level and quality of life for people with Diabetes Mellitus during the Covid-19 pandemic p-value =0.000 (p< 0.05).The research concluded that the people’s spiritual level and quality of life with diabetes mellitus are high, and there is a relationship between the people’s spiritual level and quality of life with diabetes mellitus during the Covid-19 pandemic. Suggestion: As input for further researchers to be able to investigate further the factors that affect the spiritual level of people with Diabetes MellitusAbtsrakPenderita Diabetes Melitus memiliki daya tahan tubuh lemah sehingga rentan terkena infeksi Covid-19. Diabetes Melitus menimbulkan dampak pada fisik dan psikologis yang menyebabkan penurunan kualitashidup. Kualitas hidup yang baik adalah kondisi fungsional yang optimal dari segi fisik, psikologis, lingkungan, sosialserta spiritual. Salah satu kontributor penting health-related quality of life bagi penderita Diabetes Melitus untuk mempertahankan kualitas hidup adalah spiritualitas. Spiritualitas dapat meningkatkan kesehatan penderita Diabetes Melitus dalam menghadapi masa pandemi Covid-19.Penelitian ini bertujuan untuk mengetahui hubungan antara tingkat spiritual terhadap kualitas hidup penderita Diabetes Melitus di masa pandemi Covid-19. Penelitian ini menggunakan metode deskriptif korelasi dan pendekatan cross sectional. Sampel yang digunakan sebanyak 121 orang dengan teknik pengambilan total sampling.Alat ukur yang digunakan adalah kuesioner WHOQOL-BREF dan DSESyang telah di lakukan uji validitas dan reliabilitas. Hasil perhitungan uji Chi-Square menunjukkan ada hubungan bermakna antara tingkat spiritual terhadap kualitas hidup penderita Diabetes Melitus di masa pandemi Covid-19p-value=0,000 (p<0.05).Kesimpulan penelitian didapatkan bahwa tingkat spiritual dan kualitas hidup penderita Diabetes Melitus tinggi, serta ada hubungantingkat spiritual terhadap kualitas hidup penderita Diabetes Melitus di masa pandemi Covid-19 Sebagai masukan bagi peneliti selanjutnya agar dapat meneliti lebih lanjut mengenai faktor-faktor yang mempengaruhi tingkat spiritual pada penderita Diabetes Melitus.